Present Scenario Of Micro, Small And Medium Enterprise In India - Gurpreet Kaur Kang (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2016)
Micro, Middle (little) and Medium Enterprises play a central role in the economic and social development of the country. It is also playing a key role in the development of the economy and Socialistic with its dominant, efficient, flexible and innovative entrepreneurial spirit. MSMEs contribute around 45% in the industrial output, 40% of exports, employing 60 million people; create 1.3 million jobs every year for the unemployed people. It produces more than 8,000 to 9000 quality products for the Indian and international markets. Its contribution towards GDP in 2011 was 17% which increased to 22% in 2012. This paper analyses the various challenges and opportunities associated with MSMEs in India.